If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -34 = 83 + -9x Solving -34 = 83 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -34 + 9x = 83 + -9x + 9x Combine like terms: -9x + 9x = 0 -34 + 9x = 83 + 0 -34 + 9x = 83 Add '34' to each side of the equation. -34 + 34 + 9x = 83 + 34 Combine like terms: -34 + 34 = 0 0 + 9x = 83 + 34 9x = 83 + 34 Combine like terms: 83 + 34 = 117 9x = 117 Divide each side by '9'. x = 13 Simplifying x = 13
| 65+0.06c=48+0.10c | | 2-7(4-6x)=0 | | 5x+3=-3x+19 | | -3x-13=17 | | -(b-4b)=8b-b | | 3x-1=-32 | | 2+3(4+1)= | | 16=r+20 | | 7m-34=6m-4(-7-8m) | | 3-9(8x+2)=4 | | (3x^2)x^5= | | 11x+70=-128 | | 4.7x+4.1x=-15.84 | | 3x-9y=21y | | 6.8x=11.5 | | 14x-4=18x-7 | | 7(6)+3-5(6)= | | -54=-15-3x | | 48+4y-20=17y-12-5y | | 2z-4-z=2 | | n-13=-33 | | -14x^2-49=0 | | 6x-7=8x+15 | | 3(0)+2(0)+7= | | -25=-9+x | | 56-11x=199 | | y=3x^2+10x | | 55-12x=139 | | .4w+.6=-3 | | b+16=24 | | Xy-9z=3 | | 8x+23=3x-7 |